Revitalisasi Madrasah Diniyah Awaliyah melalui Pendekatan Manajemen Berbasis Madrasah - Magdalena, Magdalena (Dinamika Ilmu, 2012)
Madrasah Diniyah Awaliyah as an Islamic educational institution is not insteresting for among Moslem society. The revitalization of Madrasah Diniyah Awaliyah can be done by Madrasah Based Management approach. The Madrasah Based Management include in put, process, and out put aspect. The input aspect includes student, teacher, headmaster, curriculum, parent, and participations of society. The process aspect is program management, institution management, leadership, madrasah comittee, organization, and accountability. The out put aspect is academic/non academic.